2018
DOI: 10.1111/obr.12775
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol supplementation significantly influences obesity measures: a systematic review and dose–response meta‐analysis of randomized controlled trials

Abstract: This study aimed to summarize earlier randomized controlled trials on the effects of resveratrol supplementation on body weight (BW), body mass index (BMI), waist circumference (WC) and fat mass (FM). We searched PubMed, SCOPUS, Cochrane Library and Google Scholar from inception to April 2018 using relevant keywords. All clinical trials investigating the effects of resveratrol supplementation on BW, BMI, WC and FM in adults were included. Overall, 28 trials were included. Pooled effect sizes suggested a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 60 publications
(140 reference statements)
0
34
1
1
Order By: Relevance
“…However, one study reached null results (Bo et al, ). In a recent meta‐analysis study including 28 trials, resveratrol supplementation showed a beneficial significant effect on weight, BMI, and WC without any significant effect on FM (Mousavi et al, ). Contrary to these findings, another meta‐analysis with fewer included studies found no significant effect of resveratrol administration on body weight and BMI (Christenson et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one study reached null results (Bo et al, ). In a recent meta‐analysis study including 28 trials, resveratrol supplementation showed a beneficial significant effect on weight, BMI, and WC without any significant effect on FM (Mousavi et al, ). Contrary to these findings, another meta‐analysis with fewer included studies found no significant effect of resveratrol administration on body weight and BMI (Christenson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It seems that some factors like type of resveratrol supplement (pure resveratrol or resveratrol‐enriched extract), supplementation dosage, intervention duration, and health status of population contributed to the contradictory findings. Furthermore, it seems that resveratrol had a positive effect in studies with an overweight or obese population (Mousavi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although this dietary pattern has been constructed by combining Mediterranean and DASH dietary patterns, it has some advantages over these eating patterns. The MIND diet uniquely emphasizes on the consumption of berries and beans, which might influence body weight because of their content of resveratrol and fiber [30,31]. In addition, low intake of calorie-dense foods, including fast and fried foods, pastries and sweets and butter and margarines, in this dietary pattern might further explain its probable beneficial effect on weight control [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…There is also some evidence that resveratrol, another polyphenol found in red wine, has potential beneficial effects on reducing weight gain. A systematic review and dose‐response meta‐analysis of randomised controlled trials ( n = 28) of resveratrol supplementation of <500 mg/day for at least 3 months, in people with obesity, found small but statistically significant reductions in weight (−0.5 kg) and waist circumference (−0.79 cm) (Mousavi et al 2019). Proposed mechanisms, mostly from animal and cell studies, include resveratrol’s antioxidant and anti‐inflammatory properties, as well as increased fatty acid oxidation, decreased fatty acid synthesis, increased thermogenesis and energy expenditure and inhibition of digestive enzymes (Farhat et al 2017).…”
Section: Potential Mechanisms Involved In Red Wine Gut Microbiota Anmentioning
confidence: 99%